The use of tennis racket media among SEA Games athletes in Cambodia: How does it affect receiving sepak takraw? - Hakim, Abdul Aziz; Saifullah, Ronny; Pelana, Ramdan; Hanafi, Moh.; Yanti, Novi (Journal Sport Area, 2024)
Background Problems: Receiving the first ball is a problem for national sepak takraw athletes at the 2023 Cambodia Sea Games, where the reception technique is in the bad category. Research Objectives: This study aims to determine the effect of using tennis racket media on SEA Games athletes in Cambodia on improving sepak takraw reception skills. Methods: This study used quantitative methods with a one-group pretest and posttest. Random sampling was used to select Cambodian SEA Games sepak takraw athletes as research subjects. The population in this study were men’s sepak takraw athletes from the 2023 Cambodia Sea Games national training, with the sample used totaling 12 athletes taken randomly. Findings and Results: The results showed that the use of tennis racket media had a significant effect on increasing acceptance of sepak takraw games. Athletes who follow the training programme with tennis racket media experience a consistent increase in their ability to receive the ball. Conclusion: These results indicate that the use of this additional training tool can be an effective strategy for improving the performance of sepak takraw athletes. The study makes some significant contributions to understanding the use of racket media in the training of sepak takraw athletes. Further research and wider experimentation can help deepen the understanding of the potential use of tennis racket media in sports training.